Reducing crystal symmetry to generate out-of-plane Dzyaloshinskii–Moriya interaction - Heng Niu; Hee Young Kwon; Tianping Ma; Zhiyuan Cheng; Colin Ophus; Bingfeng Miao; Liang Sun; Yizheng Wu; Kai Liu; Stuart S. P. Parkin; Changyeon Won; Andreas K. Schmid; et al. (Nature Communications)
Abstract The Dzyaloshinskii-Moriya antisymmetric exchange interaction (DMI) stabilises topological spin textures with promising future spintronics applications. According to crystal symmetry, the DMI can be categorized as four different types that favour different chiral textures. Unlike the other three extensively-investigated types, out-of-plane DMI, as the last type that favours in-plane chirality, remained missing so far. Here we apply point-group-dependent DMI matrix analysis to show that out-of-plane DMI exists under reduced crystal symmetry. Through strain and structure engineering, we show how C s symmetry is realized in ultrathin magnets and observe the out-of-plane DMI stabilised in-plane chirality using spin-polarized electron microscopy. Our results show that extremely low out-of-plane DMI strengths at µeV/atom are sufficient to stabilise topological spin textures, including merons and bimerons. We also demonstrate field-induced reversible control of the in-plane chirality and merons. Our findings open up untapped paths on topological magnetic textures and their potential applications.